Peningkatan Pengetahuan Keagamaan Anak Melalui Permainan Ular Tangga - Nurhasanah Nurhasanah; Mirnawati Mirnawati (Institusi Agama Islam Negeri (IAIN) Bone, 2023)
This study discusses Efforts to Increase Religious Knowledge of Students through the Snake and Ladder Game Method at Pattola Palallo Kindergarten, Macope Village, Awangpone District, Bone Regency. And this study aims to describe the implementation of snakes and ladders games in an effort to increase students' religious knowledge and to determine the increase in students' religious knowledge through snakes and ladders games at Pattola Palallo Kindergarten, Macope Village, Awangpone District, Bone Regency. This type of research is classroom action research (PTK). To obtain data in this study, data collection was carried out through two cycles. The results of this study show that, broadly speaking. The implementation of the snakes and ladders game in an effort to increase the religious knowledge of students at Pattola Palallo Kindergarten, Macope Village, Awangpone District, Bone Regency, was carried out according to the rules and stages of the game that had been planned by researchers in collaboration with teachers. The steps for implementing the snake and ladder game in this study were carried out in two cycles, and each cycle consisted of the planning stage, the action implementation stage, the observation / observation stage, and the reflection stage. Increasing students' religious knowledge through the snakes and ladders game method at Pattola Palallo Kindergarten, Macope Village, Awangpone District, Bone Regency. Based on the activeness of teachers and students in the implementation of learning with the application of playing snakes and ladders, the implementation of cycle 1 actions, the percentage of teacher activity is 76.92% (good category), and the percentage of student activity is 75.38% (good category), while in the implementation of cycle 2 actions, the percentage of teacher activity increases to 87.70% (good category), while the percentage of student activity increases to 90.77% (very good category), So there is a change in the activeness of teachers and students after reflecting on the results achieved in the implementation of cycle 1 actions. While the results of increasing students' religious knowledge through the application of playing snakes and ladders are categorized as students experiencing an increase in religious knowledge obtained by students with a percentage of, from pre-cycle 30%, and after the implementation of cycle 1 actions increased to 55% and the implementation of cycle 2 actions increased to 75%, with these results, the application of playing snakes and ladders in learning activities can improve the religious knowledge of students in Pattola Palallo Kindergarten, Macope Village, Awangpone District, Bone Regency.